Enhancement of antifungal efficacy of Bacillus subtilis AS80 by cold plasma technology - Pothi, Supachai; Sangwijit, Kanta; Pankong, Thamonwan; Anuntalabhochai, Somboon; Suebsan, Sugunya (Creative Science, 2024)
Pathogenic fungi represented in avocado and other fruit orchards rely predominantly on the application of fungicides. However, the employment of synthetic fungicides is increasingly restricted due to the harmful effects of pesticides on human health and the environment. Therefore, this research aimed to enhance the antifungal efficacy of antagonistic bacteria and to elucidate the enzyme activity underlying their inhibition of fungal development. The antagonistic bacteria, Bacillus subtilis AS80, were induced to mutate by cold plasma technology, and an assessment of antifungal activity was performed. It was found that three mutants named MT144, MT163, and MT165 exhibited significant antifungal activity, with mycelial growth inhibition of 86.3%, 85.2%, and 82.8%, respectively, while the wild type showed an inhibition of 76.4% at 14 days after inoculation. In addition, B. subtilis AS80 and antagonistic mutants exhibited chitinase, cellulase, and amylase activities. Interestingly, the MT123 mutant, which was deficient in antifungal activity, showed a contrasting phenotype, with high amylase activity but no detectable chitinase or cellulase activities. This study suggests that chitinase and cellulase are key enzymatic factors in B. subtilis AS80 and its mutants, mediating their ability to inhibit the growth of pathogenic fungi. GRAPHICAL ABSTRACT HIGHLIGHTS Cold plasma technology is an effective technique to enhance antifungal activity in Bacillus subtilis AS80, which is beneficial to use as a biocontrol agent. Chitinase and cellulase are key enzymatic factors in subtilis AS80 and its mutants, mediating their ability to inhibit the growth of pathogenic fungi.